Multiplex Capillary Denaturing High-Performance Liquid Chromatography with Laser-Induced Fluorescence Detection. (June 2001) - Xiao, W.; Stern, D.; Jain, M.; Huber, C.G.; Oefner, P.J.
Denaturing high-performance liquid chromatography (DHPLC) is a sensitive, robust, and operationally inexpensive method for the detection of single-base substitutions and small deletions and insertions. To increase sample throughput, we have developed a multiplexing strategy using fluorophores to distinguish different PCR products. The system combines recent advances in the synthesis of monolithic poly(styrene-divinylbenzene) capillary columns with four-color confocal argon ion laser-induced fluorescence detection. Depending on the change in retention caused by the fluorophores, adjustments in the analysis temperature may be required to ensure the maximum mutation detection sensitivity.